Faktor-Faktor yang Mempengaruhi Keputusan Kemitraan Petani Organik di Desa Claket - Safira Masdaramsa Ramada; Mubarokah Mubarokah; Risqi Firdaus Setiawan (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Nowadays, many people follow a healthy lifestyle and preserve the environment, increasing consumption of organic products and organic land in Indonesia. Consumers of organic products state the need for quality assurance in organic products. In contrast, many farmers have limited information about organic quality assurance and organic farming procedures. Education can be carried out through partnerships between organic farming companies and farmers. A partnership system is needed as an alternative effort for farmers and companies to overcome farming problems—the partnership relationship implemented between organic farmers and CV. Reja Mayur has existed for 6 years, starting in 2018. However, despite the growing public interest in organic products, the number of farmers participating in this partnership has decreased. This research aims to analyze factors influencing the decision-making of organic farmers in Claket Village regarding establishing a partnership with CV. Reja Mayur. The study took place between November and December 2023. The technique applied to define the number of respondents is “census,” which means the sample includes the entire population. The sample size used was 11 respondents, the number of CV Reja Mayur partner farmers until 2023. Data were analyzed using SEM-PLS by WarpPLS 7.0. The analysis demonstrated that personality (X1) and creative thinking (X3) significantly and positively affected farmers' decisions to join a partnership (Y). However, the participatory management style (X2) demonstrates a positive yet insignificant influence on farmers' decisions to join a partnership (Y).